2011
DOI: 10.1080/13607863.2010.508771
|View full text |Cite
|
Sign up to set email alerts
|

Religion, health beliefs and the use of mental health services by the elderly

Abstract: Further studies should evaluate the lower tendency of elderly people with religious affiliations to seek treatment for mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
0
26
1
1
Order By: Relevance
“…Kim-Goh interviewed 50 Korean clergymen with an average duration in ministry of more than 20 years and found that nearly half of them (44%) have never made a referral to a mental health service provider and those with religious conceptualization of psychiatric symptoms are less willing to make referrals for mental health treatment than those with a psychological conceptualization (Kim-Goh, 1993). Also, Ng, Nyunt, Chiam, and Kua (2011) reported that compared to those with no religious affiliation, while elderly people with religious affiliations showed higher prevalence of mental health problems, they reported less frequent treatment by health care professionals. In fact, Christians and Moslems were least likely to seek treatment for mental illness among various religious affiliations.…”
Section: Discussionmentioning
confidence: 99%
“…Kim-Goh interviewed 50 Korean clergymen with an average duration in ministry of more than 20 years and found that nearly half of them (44%) have never made a referral to a mental health service provider and those with religious conceptualization of psychiatric symptoms are less willing to make referrals for mental health treatment than those with a psychological conceptualization (Kim-Goh, 1993). Also, Ng, Nyunt, Chiam, and Kua (2011) reported that compared to those with no religious affiliation, while elderly people with religious affiliations showed higher prevalence of mental health problems, they reported less frequent treatment by health care professionals. In fact, Christians and Moslems were least likely to seek treatment for mental illness among various religious affiliations.…”
Section: Discussionmentioning
confidence: 99%
“…However, education was reported as a factor in whether older persons sought treatment. Those less formally educated were found to have stronger religious affiliations (Ng et al, 2011). Level of education was also found to be an important factor in Minhat and Amin's (2012) study of leisure participation of elderly persons in Malaysia.…”
Section: Critiquementioning
confidence: 96%
“…Elsewhere, a study by Ng, Nyunt, Chiam, and Kua (2011) of elderly persons in Singapore suggested that religious beliefs could affect health beliefs and the use of mental health services. Compared to those with no religious affiliation, elderly persons with religious affiliations showed higher prevalence of mental health problems, yet reported less frequent treatment by healthcare professionals.…”
Section: Critiquementioning
confidence: 97%
“…Religious beliefs may also affect medical decision making, generate beliefs that conflict with medical care, induce spiritual struggles that create stress and impair health outcomes, and interfere with disease detection and treatment compliance (8). Most of the studies conducted in Asia have focused on help-seeking behavior among people with mental health problems (16)(17)(18)(19) or the role of religion and spirituality in coping with mental health problems (20,21).…”
mentioning
confidence: 99%